2008
DOI: 10.1073/pnas.0804277105
|View full text |Cite
|
Sign up to set email alerts
|

Direct transformation from amorphous to crystalline calcium phosphate facilitated by motif-programmed artificial proteins

Abstract: An animal's hard tissue is mainly composed of crystalline calcium phosphate. In vitro, small changes in the reaction conditions affect the species of calcium phosphate formed, whereas, in vivo, distinct types of crystalline calcium phosphate are formed in a wellcontrolled spatiotemporal-dependent manner. A variety of proteins are involved in hard-tissue formation; however, the mechanisms by which they regulate crystal growth are not yet fully understood. Clarification of these mechanisms will not only lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 27 publications
13
138
3
1
Order By: Relevance
“…This observation is also in agreement with the literature [7]. This amorphous substance is most likely amorphous calcium phosphate (ACP) [39], amorphous calcium carbonate (ACP), or amorphous calcium carbonate phosphate (ACCP) [40]. In recent years, it has been shown in many articles [35,[40][41][42][43] that some biominerals in the form of single crystals are not formed from the saturated solutions of their building ions, but from the precursor amorphous phase.…”
Section: Xrd Results-discussionsupporting
confidence: 79%
“…This observation is also in agreement with the literature [7]. This amorphous substance is most likely amorphous calcium phosphate (ACP) [39], amorphous calcium carbonate (ACP), or amorphous calcium carbonate phosphate (ACCP) [40]. In recent years, it has been shown in many articles [35,[40][41][42][43] that some biominerals in the form of single crystals are not formed from the saturated solutions of their building ions, but from the precursor amorphous phase.…”
Section: Xrd Results-discussionsupporting
confidence: 79%
“…Herein, combined with the FT-IR results, it is reasonable to assume that, Asp-rich biomolecules may switch on the crystallization reaction. However, the previous studies of biomimetic mineralization show that Asp-rich peptides and other organic matrices often inhibit crystallization despite that a few of them can accelerate the nucleation at low concentrations (27)(28)(29)(30). It is even demonstrated that the cooperation of magnesium and associated proteins can stabilize the amorphous phases more (4,10,31).…”
Section: Resultsmentioning
confidence: 99%
“…Using in situ AFM and optical microscopy, Galkin et al (10) and Kuznetsov et al (11) then showed that both protein and virus crystals could form via a two-step process during both homoepitaxy (11) and bulk crystallization (10). Subsequently, the significance of amorphous or dense-liquid precursors was extended to inorganic systems, particularly biomineral phases, such as calcium carbonate and calcium phosphate generated both in vivo (24,27) and in vitro (25), as well as other inorganic (27) phases. Most recently, the existence of stable prenucleation clusters (26) in bulk solutions of calcium carbonate has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since ten Wolde and Frenkel (9) first used simulations to predict a two-step process for protein crystallization, the importance of nonclassical, multistage crystallization pathways has become increasingly evident in experimental studies of proteins (10) and viruses (11), as well as biominerals (23)(24)(25)(26) and other inorganic (27) phases. In the simulations (9), critical point fluctuations near a liquid-liquid coexistence line led to formation of unstable dense-liquid droplets in which crystalline nuclei could eventually form.…”
Section: Discussionmentioning
confidence: 99%